Inflation properties in count data distributions: a three-decade bibliometric analysis - Razik Ridzuan Mohd Tajuddin,; Noriszura Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Researchers have been proposing inflated models for count data since 1992, which was pioneered by Diane Lambert. In inflated models for count data, the inflation points commonly occurs either at zero and/or one. A comprehensive bibliometric analysis has been conducted to investigate how popular the studies on inflated models have been since 1992. A total of 724 documents have been retrieved from Scopus database, which include all types of documents and languages. The publications growth rate for the inflated count data models was 16.27%, proving that many researchers were attracted to this area of study. Majority of the documents were articles and written in English. One article published in the R Journal has obtained the most acceptance among the community as seen from the average number of citations each year. The United States of America may have been collaborating with lots of researchers from other countries but the University of São Paulo, Brazil has published the greatest number of documents related to the inflated count data models.